Dilemma of State Schools in Sri Lanka: How School Type Creates Inequality in Academic Achievement - Herath, Jeevani (National Education Research and Evaluation Centre, 2022)
State schools in Sri Lanka are categorized into four types based on the grades and subjects offered at the General Certificate of Education – Advanced/Level (G.C.E. A/L). This categorization appears to be providing equity in educational access as there are fair policies to enroll students into any type of school. Unfortunately, there are many other hidden contributing factors which shatter these fair policies concerning equity in school access. Moreover, various studies have shown that student achievement levels can be easily determined by the type of school they attend. This study was done using data collected by the National Education Research and Evaluation Centre (NEREC) in collaboration with the World Bank and the Ministry of Education (MoE) in Sri Lanka in 2012 on factors affecting educational achievement of students completing grade 8. For this study, such data were extracted by creating parameters for social capital, human capital and financial capital. Each capital was correlated with the marks for science, mathematics and English to ascertain whether any relationship between capital and achievement exists. It was found from the study that rather than improving home and school social capital, improving home and school financial and human capital can heighten academic achievements.
Keywords: School type; Capital; Educational achievement